Creating democratic education in neo¬liberal and neoconservative times de Michael Apple. Obert, G. y Eliggi, G. (Traductoras) (Praxis Educativa, 2014)
We live in a time when the very meaning of democracy is being radically changed. Democracy is indeed a contested concept; it is at the center of struggles over what the goals of education should be, how it should be done and this is not only about schools. It is about what kind of society we want and what kinds of politics will help us get there. We wonder: Can education change society? analyzing the role of schools inside economy, the crucial site for creating activist identities among oppressed people; the large part of their lives students spend inside schools where they come to grips with authority relations, to be with others who are both the same and different; what is socially valued as “legitimate knowledge” and what is seen as merely “popular”; recognition over race/ethnicity, class, gender, sexuality, ability, religion, and other important dynamics of power. An example to think about education policies and their role in social transformation can be found in the city of Porto Alegre in Brazil.
Keywords: democracy; democratic schools; struggles; power; dominance